Pengaruh Economic Value Added (EVA), Net Profit Margin (NPM), Free Cash Flow (FCF), dan Struktur Modal Terhadap Return Saham - Kustanti, Amelia Dwi; Mulya, Anissa Amalia (Economics and Digital Business Journal, 2024)
This study aims to determine the effect of economic value added, net profit margin, free cash flow, and capital structure on stock returns. The population in this study is infrastructure sector companies listed on the Indonesia Stock Exchange in the financial statements for the 2018-2022 period. The sampling technique in this study used the purposive sampling method and was obtained by 41 companies. The analysis technique used is multiple linear regression analysis using SPSS software version 22.0. The results of this study show that Economic Value Added, Net Profit Margin, and Free Cash Flow have a positive and significant influence on Stock Return, while Capital Structure has a negative and significant influence on Stock Return